Unlocking Digitalization in Forest Operations with Viewshed Analysis to Improve GNSS Positioning Accuracy - Lopatin, Eugene; Väätäinen, Kari; Kukko, Antero; Kaartinen, Harri; Hyyppä, Juha; Holmström, Eero; Sikanen, Lauri; Nuutinen, Yrjö; Routa, Johanna (MDPI AG, 2023)
This study evaluated the positioning accuracy of moving forest harvesters using global navigation satellite system (GNSS) signals under a forest canopy, and developed approaches for forecasting accuracy under a mature spruce canopy cover. Real-time kinematic positioning with a Trimble R12 receiver on top of a harvester achieved high positioning accuracy, with 86% of observations meeting a maximum precision of 8 mm. However, the presence of a canopy cover hampered the GNSS’s performance as there were fewer satellites available, leading to an increased number of inaccurate positions and larger values of the dilution of precision in geometry (GDOP), position (PDOP), vertical (VDOP) and horizontal directions (HDOP). The canopy cover estimated from the viewshed analysis of the digital surface model (DSM) was found to be a significant predictor of the dilution of precision and maximum deviation from the true position. These findings suggest that viewshed analysis provides more precise results than a mere canopy cover percentage for evaluating the impact of canopy cover on the GNSS’s positioning of a harvester, despite its computational demands. Developing intelligent algorithms for precise positioning under the canopy can facilitate autonomous harvesting and forwarding, allowing for the implementation of digitalization in forest operations.
Keywords: digitalization; forest operations; viewshed analysis; GNSS positioning accuracy; harvester; canopy cover; forecasting accuracy; autonomous harvesting